SPONTANEOUS RIGHT CORONARY ARTERY DISSECTION IN A NORMOTENSIVE POST-PARTUM FEMALE - Ishtiaq, Rizwan; Saddique, Asim; Akram, Ali; Arif, Mariam; Muhammad, Fida; Chaudhry, Umer Hassan (Journal of Ayub Medical College Abbottabad, 2018)
Acute myocardial infarction following coronary artery dissection during the post-partum period is a rare entity. Greater hemodynamic stress and hormonal changes increase the risk of developing a coronary artery dissection post-partum. Herein, we report the first case of a normotensive patient from Pakistan that presented with inferior wall myocardial infarction following 10-days post-partum due to right coronary artery dissection. This article highlights the importance of prompt diagnosis and subsequent life-saving treatment. Keywords: myocardial infarction; post-partum; coronary artery dissection; right coronary artery